Social and ethnic segregation in the Paris metropolitan area at the beginning of the 21st century - Grzegorczyk Anna (Miscellanea Geographica: Regional Studies on Development, 2013)
Although the socio-spatial aspect of cities in the globalisation era has gained a new dimension, it cannot be explained by the globalisation process alone. The article presents the problem of social and ethnic segregation in Île-de-France between 1999 and 2009. Socio-economic and demographic data are used to measure indices of segregation and the description of characteristic chosen districts to show its spatial inertia. The analysis revealed a higher degree of social segregation in the entire Paris metropolitan region than in the city of Paris itself. The upper class is the most segregated group, followed by foreigners, immigrants and the lower class. The pattern emphasises the important role of autosegregation factors and functions. It is observed that a constant division into homogenous parts exists in the prestigious and affluent western districts and the impoverished immigrant north-eastern districts. Socio-spatial tendencies reveal the growing importance of the upper class.